How funnel chanterelle (Craterellus tubaeformis) became an urban forager favorite in Scandinavia - Ingvar Svanberg; Mai Løvaas; Sabira Ståhlberg (Journal of Ethnobiology and Ethnomedicine)
Abstract Background Peasants in preindustrial Norway and Sweden refused to touch edible macrofungi even during times of scarcity or famines, although this free food resource was abundantly available and authorities encouraged gathering mushrooms to enrich the diet since the eighteenth century. Urbanization and gradual changes of attitudes have turned mushroom gathering in forests and meadows into an important leisure activity. In recent decades, city foragers have discovered the funnel chanterelle, Craterellus tubaeformis (Fr.) Quél. This delicious edible mushroom has quickly become one of the most popular species for hobby gatherers. Our article follows the journey of the funnel chanterelle from an ignored food resource to a popular seasonal delicacy served also in luxury restaurants, discussing how, when and why attitudes and habits have changed. Methodology For the historical background, this qualitative ethnomycological study uses a rich corpus of newspapers in the Swedish and Norwegian newspaper databases at the Swedish and Norwegian National Libraries. Data on contemporary mushroom hunter knowledge of C. tubaeformis have been obtained from responses to a questionnaire from 2017 with a hundred respondents. The study has also benefited from the authors’ participatory observations, own experiences as mushroom gatherers, and conversations with mushroom pickers in Norway and Sweden. Cookery books, mushroom identification guides and other printed works have also been utilized. Results Urbanization caused a change in the relationship with nature: urban foragers are a fairly new phenomenon in Sweden and Norway but they have significant impact on food habits. City foragers discovered and have focused extensively on the funnel chanterelle ever since the end of the 1970s. It is now one of the most popular edible mushrooms in Sweden and Norway, widely publicized in newspapers, discussed in evening classes for novice mushroom gatherers, and presented in books and TV and internet food shows. Media and in recent decades also internet can be identified as the main information sources for urban gatherers. Attitudes have changed among others due to transformations in lifestyle, internationalization, and the fashion of consuming more local foods, as well as a strong need for leisure and perceiving nature as the best place for it, and gathering as a meaningful activity in nature. Conclusions The funnel chanterelle is easy to identify, harvest and prepare. It is regarded as wild food with a wide range of uses, harvested for both personal consumption and commercial purposes, and now well-integrated in the Nordic cuisine. The urban population perceives mushrooms and various other wild foods as a normal part of the diet and modern food, in contrast to their peasant ancestors who thought fungi were animal food only. Contemporary human-fungi relations in Scandinavia have multiple meanings, not only as a food source but also as a recreational activity, maintaining emotional ties to the forests and nature among a highly urbanized population.